Maximizing Finance for Development : Impact Bonds for Water and Sanitation in Latin America and the Caribbean - World Bank (Washington, DC, 2022)
The maximizing finance for development (MFD) approach can be implemented to close the financing gap in the water and sanitation sector in Latin America and the Caribbean, helping the region in getting closer to achieving sustainable development goal (SDG 6), particularly if emphasis is put on innovative financing, and linking SDG financing principles. In this overall context, impact bonds are some of the latest tools made available in the results-based financing (RBF) area. On the supply side, impact bonds can inject a more entrepreneurial approach into public service provision. By focusing on outcomes rather than activities, service providers are offered more latitude in the way they deliver services. Through a review of the most recent studies and research on the matter, this document explores the challenges faced by Latin America and the Caribbean in financing the development of its water and sanitation sector and its need for new instruments. It provides insights on impact bonds as one of the latest innovations in the field of RBF. Limitations of the evaluation include the fact that the instrument is rather young. Chapter one looks at the challenges faced by Latin America and the Caribbean in achieving SDG 6. Chapter two examines the financing gap and how new instruments, and innovative thinking can help tackle it. Chapter three explores a new paradigm, the emergence of impact bonds. Chapter four closes the loop by looking at how impact bonds can be a useful complement to closing the financing gap. The final chapter offers recommendations for the development of this relatively new instrument.